Development of a Scouting Pocket Book Application as an Innovation to Enhance Students Character Education in Islamic Boarding Schools - Cibro, Andika Novriadi; Mardianto, Mardianto; Arsyad, Junaidi (Fitrah: Journal of Islamic Education, 2024)
The Pesantren scout handbook application in Aceh was developed to strengthen santri character learning. However, its implementation still faces obstacles in the form of limited technological infrastructure, low digital literacy of scout leaders, and challenges of integration with the traditional pesantren curriculum. This study aims to develop a scout pocket book application as a medium for learning the character of students, as well as testing its feasibility and effectiveness in the pesantren environment. The method used is Research and Development research with stages of data collection, design, product development, and evaluation based on literature review and previous research findings. The results show that this application is able to present scouting material and character values interactively through text, videos, and quizzes, and allows real-time monitoring of santri development. The app is considered feasible and potential as a systematic, flexible, and technology-based character learning instrument. The implication is that funding support and collaboration with the government and private sector are important to encourage digital literacy in pesantren and strengthen character education in the digital era.